p75 neurotrophin receptor regulates craniofacial growth and morphology in postnatal development - Zhao, Byron; Suh, Jinsook; Zhang, Yan; Yin, Eric; Kadota-Watanabe, Chiho; Chang, In Won; Yaung, Jun; Lao-Ngo, Isabelle; Young, Nathan M.; Kim, Reuben H.; Klein, Ophir D.; Hong, Christine (Frontiers in Cell and Developmental Biology, 2025)
Craniofacial abnormalities are among the most prevalent congenital defects, significantly affecting appearance, function, and quality of life. While the role of genetic mutations in craniofacial malformations is recognized, the underlying molecular mechanisms remain poorly understood. In this study, we investigate the role of p75 neurotrophin receptor (p75NTR) in craniofacial development by comparing wild-type (p75NTR+/+) mice against p75NTR-deficient (p75NTR−/−) knockout mice. We employed histology, micro-CT surface distance, volumetric analysis, and geometric morphometric analysis to assess craniofacial development and growth. On postnatal day 7 (P7), p75NTR−/− mice exhibited reduced skull length compared to wild-type controls. By P28, micro-CT analysis revealed significant reductions in calvarial bone volume and trabecular bone thickness in p75NTR−/− mice. Geometric morphometric analysis identified significant shape alterations in the nasal, parietal, and occipital regions, with p75NTR−/− mice showing a shortened cranium and tapered nasal bone morphology. These findings highlight the critical role of p75NTR in regulating postnatal craniofacial development. Disruption of p75NTR signaling impairs both the growth and morphological integrity of craniofacial structures, which may contribute to the pathogenesis of congenital craniofacial abnormalities. In the future, a better understanding of the molecular mechanisms through which p75NTR mediates craniofacial development may offer valuable insights for future targeted therapeutic strategies for craniofacial defects.